2019
DOI: 10.1177/0003489419875473
|View full text |Cite
|
Sign up to set email alerts
|

Sterno-omohyoid Free Flap for Dual-Vector Dynamic Facial Reanimation

Abstract: Background: Dynamic rehabilitation of longstanding facial palsy with damaged, atrophied, or absent facial muscles requires replacement of neural and muscular components. The ideal reconstruction would include a fast-twitch muscle that is small, a reliable donor vessel and nerve, and the potential to provide a natural, synchronous, dentate smile with minimal donor site morbidity. Many flaps have been successfully used historically, but none has produced ideal rehabilitation. Objective: To evaluate the novel ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Alam et al 47 first reported the use of a novel sternohyoid muscle free flap using the ansa cervicalis for nerve coaptation and the superior thyroid artery as its vascular pedicle in a series of 24 fresh cadaver flap harvest procedures. Vincent et al 48 later described a dual vector transfer technique using the sternohyoid and omo-hyoid muscles together in cadaveric studies and report good outcomes with one patient who successfully underwent a dual-vector sterno-omohyoid flap with the superior thyroid artery, middle thyroid vein, and ansa cervicalis innervated by the nerve to masseter. Alegret et al 49 reported a sternohyoid flap innervated by the hypoglossal nerve in a single case.…”
Section: Novel Flaps For Dynamic Reanimationmentioning
confidence: 99%
“…Alam et al 47 first reported the use of a novel sternohyoid muscle free flap using the ansa cervicalis for nerve coaptation and the superior thyroid artery as its vascular pedicle in a series of 24 fresh cadaver flap harvest procedures. Vincent et al 48 later described a dual vector transfer technique using the sternohyoid and omo-hyoid muscles together in cadaveric studies and report good outcomes with one patient who successfully underwent a dual-vector sterno-omohyoid flap with the superior thyroid artery, middle thyroid vein, and ansa cervicalis innervated by the nerve to masseter. Alegret et al 49 reported a sternohyoid flap innervated by the hypoglossal nerve in a single case.…”
Section: Novel Flaps For Dynamic Reanimationmentioning
confidence: 99%